Kuis Kata Baku dan Padanan Istilah Sebagai Sarana Inovatif Dalam Pembinaan Bahasa Indonesia Pada Akun Media Sosial Instagram @07_Karang_Taruna - I Made Alvin Fadliansyah; Fira Pebriyani; Uah Maspuroh (Peneliti.net, 2023)
Language is a communication tool used to interact by humans. In this case, the language has many variations, especially in Indonesia. With so many languages ​​in various regions, Indonesia has created a unified language, namely Indonesian. This study examines how people's ability to speak Indonesian according to KBBI V by using the Instagram social media account @07_Karang_Taruna. The methods and approaches used in this research are qualitative methods and descriptive qualitative approaches. The results of the data obtained in this study, namely the ability to speak standard words and equivalent terms followers of the social media account @07_Karang_Taruna are fairly understanding standard words and equivalent terms.